Sugarcane Plant Nutrient Diagnosis - J. Mabry McCray; Ronald W. Rice; Ike V. Ezenwa; Timothy A. Lang; Les Baucum (EDIS)
Revised! SS-AGR-128, a 14-page illustrated fact sheet by J. Mabry McCray, Ronald W. Rice, Ike V. Ezenwa, Timothy A. Lang, and Les Baucum, assists sugarcane growers make improved decisions regarding fertilization through the use of leaf nutrient analysis along with visual evaluation of malnutrition symptoms to complement a soil testing program. Includes references. Published by the UF Department of Agronomy, December 2009.